Improvement of physical, mechanical and strength behavior of cohesive soils with natural pozzolana and brick dust - Chang, E. (2020)
This research project seeks to improve soil properties through experimentation with geotechnical purposes. For this, will be used natural volcanic pozzolana in 5%, 10%, 15% and brick dust in 10% giving it a second reuse. The soil improvement will be analyzed with the proposed additions and its influence on the results. It is concluded that the addition improves the behavior of the soil by decreasing its plasticity index, increases the compaction index and improves the geotechnical parameters.